Interaction between the hypothalamo-pituitary-adrenal and thyroid axes during immobilization stress - Kadhim, Hakeem J.; Kuenzel, Wayne J. (Frontiers in Physiology, 2022)
The timing of major components of the hypothalamo-pituitary-thyroid (HPT) axis was compared to those of the avian HPA axis. Chicks, Gallus gallus, 5 weeks of age were subjected to immobilization (IM) stress. Blood, brain, and APit were sampled prior to stress (controls) and 15, 30, 60, 90, and 120 minutes (m) following IM. The NHpC and paraventricular nucleus (PVN) were cryodissected from brain sections for RT-qPCR determination. Gene expression of thyrotropin-releasing hormone (TRH) and its receptors (TRH-R1 and TRH-R3), urocortin3 (UCN3), deiodinase 2 (D2), and the second type of CRH named CRH2 within the NHpC and PVN was measured. Additionally, gene expression of thyroid-stimulating hormone β (TSHβ), and D2 were determined in the APit. Results supported concurrent activation of major brain and APit genes associated with the HPA and HPT axis following IM. Within the NHpC, UCN3 and CRH, displayed an early peak in mRNA synthesis following IM. In the APit, TSH mRNA significantly increased at 15m, peaked at 30m and returned to baseline quantities thereafter. This matched closely the APit response of the HPA axis production of heteronuclear and mRNA POMC following stress. Both TRH-R1 and TRH-R3 mRNA synthesis in the APit significantly increased at 15m and remained significantly elevated through the remaining sampling points. In the NHpC, TRH-R1 mRNA significantly increased 15m after IM and TRH-R3 mRNA significantly increased at 60 and 90m while no significant changes occurred in the PVN. In contrast, CRH2 displayed significantly increased mRNA production at 60, 90 and 120m in the NHpC and at 120m in the PVN. The delayed, significant increase in D2 mRNA in the NHpC at 60m and increase in APit D2 mRNA at 60m and significant increase at 120m may have impacted TRH gene expression. Overall, CRH and UCN3 appear to display an early activation of TSHβ in the APit while TRH and CRH2 show a delayed, sustaining effect. Therefore, data indicate that not only CRH neurons and corticotropes/thyrotropes but also TRH neurons, related peptides and thyrotropes are activated concurrently to return the body to a homeostatic setting in response to stress.